Perancangan Interior Language Learning Centre di Bali - Dinda Tamara Indrawardani; Hedy Constancia Indrani; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
Nowadays, the number of people interested on learning foreign language is increasing to the demands of globalization that require individuals to equip themselves with more insight in order to compete globally and become potential human resources. In addition, many high school and college students who have great desire to be able to study overseas and even settled there. This has led many non-formal education institutions to offer systems and learning materials as preparation for the community to learn a foreign language. Language Learning Center is a non-formal institution to help provide preparatory education for students and students to be able to communicate well using a foreign language. Presented with recreational educational activities for youth and adults with activity support facilities such as classroom, study hall, library, interview room, recreation room, cafetaria and other supporting facilities. Designed using different color schemes in each area to provide different experience and surprises in the move. This is encouraging users to be more active and enjoy every interaction and activities that occur in each area. Design method using design thinking process consist of (1) Inspiration (Understand, Observe and Point of View), (2) Ideation (Ideate, Prototype, and Test), (3) Implementation (Story Telling, Pilot, and Business Model) . Then the basic design comes from the literature as a reference theory in the design of Language Learning Center.